219. DIFFERENT CLINICAL SYMPTOM PATTERNS IN PATIENTS WITH REFLUX MICRO-ASPIRATION CONFIRMED BY NEW PULMONARY ASPIRATION SCINTIGRAPHY TECHNIQUE. (24th September 2022) - Khoma, Oleksandr; Park, Jin-soo; Lee, Felix; Van der Wall, Hans; Falk, Gregory L
Abstract: Little primary reported data exists on presenting symptoms of patients in whom reflux micro-aspiration is confirmed. The aim of this study is to report symptoms and presenting patterns of a large group of patients with confirmed reflux micro-aspiration. Data was extracted from a prospectively populated database of patients referred to a tertiary centre with severe refractory, or atypical reflux (laryngopharyngeal reflux). Patients with reflux micro-aspiration on new technique scintigraphy were included. A comparator group of patients with proven proximal reflux to the level of pharynx when supine and/or upright was also included. Inclusion criteria were met by 243 patients with confirmed reflux micro-aspiration (33% males; mean age 59, range 17–88). Most common symptoms amongst patients with micro-aspiration were regurgitation (72%), cough (67%), heartburn (66%), throat clearing (65%), and dysphonia (53%). The most common two-symptom combinations were heartburn/regurgitation, cough/throat clearing, regurgitation/throat clearing, cough/regurgitation and dysphonia/throat clearing. The most common three-symptom combinations were cough/heartburn/regurgitation, cough/regurgitation/throat clearing and dysphonia/regurgitation/throat clearing. Cluster analysis demonstrated two main symptom groupings, one suggestive of proximal volume reflux symptoms and the other with motility/inflammatory bowel syndrome (IBS)-like symptoms (bloat, constipation). Combination of typical symptoms of GORD such as heartburn or regurgitation and a respiratory or upper aero-digestive complaint such as cough, throat clearing, or voice change should prompt consideration of reflux micro-aspiration. Atypical reflux symptoms may result from IBS-type abnormality.